Learning from MARQuIS: future direction of quality and safety in hospital care in the European Union. (2nd February 2009) - Groene, O; Klazinga, N; Walshe, K; Cucic, C; Shaw, C D; Suñol, R
Abstract : This article summarises the significant lessons to be drawn from, and the policy implications of, the findings of the Methods of Assessing Response to Quality Improvement Strategies (MARQuIS) project—a part of the suite of research projects intended to support policy established by the European Commission through its Sixth Framework Programme. The article first reviews the findings of MARQuIS and their implications for healthcare providers (and particularly for hospitals), and then addresses the broader policy implications for member states of the European Union (EU) and for the commission itself. Against the background of the European Commission's Seventh Framework Programme, it then outlines a number of future areas for research to inform policy and practice in quality and safety in Europe. The article concludes that at this stage, a unique EU-wide quality improvement system for hospitals does not seem to be feasible or effective. Because of possible future community action in this field, attention should focus on the use of existing research on quality and safety strategies in healthcare, with the aim of combining soft measures to accelerate mutual learning. Concrete measures should be considered only in areas for which there is substantial evidence and effective implementation can be ensured.